From Activists to Illegally Occupying Land: Aboriginal Resistance as Moral Ecology in Perth, Western Australia - Cox, Shaphan; Birdsall-Jones, C. (Palgrave Macmillan, Cham, 2019)
The criminalisation of Aboriginal people when asserting their sovereign right to place continues to operate in settler-states such as Australia. This chapter responds to Jacoby’s call for a closer engagement with scholarly work on settler colonialism in the context of moral ecology. Through an analysis of a protracted dispute over the redevelopment of a Brewery building in Perth, Western Australia this chapter explores the occupation of the site by Nyoongar Aboriginal activists seeking to protect their sacred site. Long after the occupation has been removed and the redevelopment completed a settler colonial critique of events reveals how inversions come to dominate public discourse where the state becomes the hosts while original inhabitants who have survived, managed and cared for the land are excluded. The chapter concludes with the possibility of reimagining contested claims to place in the city.